2023
DOI: 10.3390/insects14020198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soldiers on Exploratory Foraging Behavior in the Formosan Subterranean Termite, Coptotermes formosanus (Blattodea: Rhinotermitidae)

Abstract: Termites are eusocial insects that live in organized colonies consisting of reproductives, workers, and soldiers. Soldiers are specialized for defense but are expensive to maintain, as they are incapable of husbandry and must be fed and groomed by workers. The soldiers of several species influence foraging behavior by acting as scouts that initiate foraging or by mediating worker behavioral plasticity during food exploration. These behaviors imply that soldiers may play a keystone role in termite colony functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…A higher number or proportion of soldiers could reduce the potential predation risk, preventing the cost of foraging during the early phase (Almeida et al, 2016) and may improve the decision of foraging (Sacramento et al, 2020). Despite the aforementioned studies reported the effect of soldiers in foraging, a recent study, however, showed that the presence of soldiers and different proportions of soldiers in C. formosanus did not affect the tunneling behaviors of workers (McCarthy et al, 2023). Therefore, it is possible that the proportion of soldiers in the foraging group could be set intrinsically at 10-20%, to maximize the protection of foraging workers from predation risk while limiting the burden on workers.…”
Section: Discussionmentioning
confidence: 98%
“…A higher number or proportion of soldiers could reduce the potential predation risk, preventing the cost of foraging during the early phase (Almeida et al, 2016) and may improve the decision of foraging (Sacramento et al, 2020). Despite the aforementioned studies reported the effect of soldiers in foraging, a recent study, however, showed that the presence of soldiers and different proportions of soldiers in C. formosanus did not affect the tunneling behaviors of workers (McCarthy et al, 2023). Therefore, it is possible that the proportion of soldiers in the foraging group could be set intrinsically at 10-20%, to maximize the protection of foraging workers from predation risk while limiting the burden on workers.…”
Section: Discussionmentioning
confidence: 98%